2009
DOI: 10.1177/0960327109350666
|View full text |Cite
|
Sign up to set email alerts
|

An atropine and glycopyrrolate combination reduces mortality in organophosphate poisoning

Abstract: Anticholinergics are the mainstay of the pharmacological management of organophosphate poisoning (OPP). Atropine has the potential to cause central toxicity which may complicate the management of this life-threatening condition. A combination of atropine and glycopyrrolate in equivalent dosages titrated to the peripheral muscarinic signs, theoretically reduces the central effect of the anticholinergics by 50% and thereby the risk of central toxicity, while it provides effective control of the peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Atropine can cause a range of doserelated adverse effects 50 . It crosses the BBB easily and central signs of atropine toxicity are common complications in humans treated with high doses 3 . The very high doses necessary to treat aldicarb poisoning effectively in dogs may result in neurological complications such as drowsiness, ataxia, seizures and respiratory depression.…”
Section: Atropine Sulphatementioning
confidence: 99%
See 2 more Smart Citations
“…Atropine can cause a range of doserelated adverse effects 50 . It crosses the BBB easily and central signs of atropine toxicity are common complications in humans treated with high doses 3 . The very high doses necessary to treat aldicarb poisoning effectively in dogs may result in neurological complications such as drowsiness, ataxia, seizures and respiratory depression.…”
Section: Atropine Sulphatementioning
confidence: 99%
“…Glycopyrrolate Glycopyrrolate could be considered as an alternative drug to atropine for the treatment of aldicarb toxicity 6,33 , or it could also be used in combination with atropine 3 . It is a quaternary ammonium anti-muscarinic agent 33 and is registered for use in dogs and cats as a pre-anaesthetic agent to treat sinus bradycardia, sino-atrial arrest and incomplete atrioventricular (AV) block 50 .…”
Section: Atropine Sulphatementioning
confidence: 99%
See 1 more Smart Citation
“…Atropine has the potential to cause central toxicity which may complicate the management of cardiomyopathy (11). It has been reported that atropine may cause aspiration pneumonia through induction of the swallowing disorder and inhibition of the cough reflex (12), and it is associated with a higher incidence of a transient rash (13).…”
Section: Introductionmentioning
confidence: 99%
“…1 Atropine, a frequently used anticholinergic drug in eye clinic, was reported to have adverse effects on human eyes. 7,8 However, little has been known about the effect of atropine on the cornea. In order to provide a reference for secure medication of atropine, the present study was intended to evaluate the cytotoxicity of atropine to HCE cells using an in vitro model of non-transfected HCE cells, verify the cytotoxicity using an in vivo model of cat corneas, and clarify its possible cellular and molecular cytotoxic mechanisms in vitro.…”
Section: Discussionmentioning
confidence: 99%